1990
DOI: 10.1111/j.1440-1754.1990.tb02396.x
|View full text |Cite
|
Sign up to set email alerts
|

Transanal and intraperitoneal prolapse in intussusception

Abstract: An infant with intussusception who developed an unusual complication of transanal and intraperitoneal prolapse is reported. Complete venous occlusion of the intussusceptum for a prolonged period in a patient with congenital anomalous vascular supply of the colon is suggested as a mechanism responsible for rupture of the intussuscepiens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…There is an association of Hirschsprung disease or its variants in the colon distal to the site of perforation due to delay of craniocaudal migration of ganglion cells, and apparently these patients may not have overt symptoms and may look deceptively healthy. It is therefore suggested that all cases of pediatric colonic perforations should be biopsied from distal part of the colon as well as rectum to rule out Hirschsprung disease or its variants as an associated anomaly [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is an association of Hirschsprung disease or its variants in the colon distal to the site of perforation due to delay of craniocaudal migration of ganglion cells, and apparently these patients may not have overt symptoms and may look deceptively healthy. It is therefore suggested that all cases of pediatric colonic perforations should be biopsied from distal part of the colon as well as rectum to rule out Hirschsprung disease or its variants as an associated anomaly [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of antimesenteric perforation in our case can be explained by the fact that isolated terminal ileal stricture development has caused chronic distention of ileum immediate proximal to the stricture. Marginal artery of the colon gives long and short terminal branches to the and their anastomoses across the antimesenteric are meagre, constituting a zone of relative ischemia, making this site of perforation during massive distention and associated inflammation at the borders of the Payer's patches [7,8]. Most likely site for perforation would be where the anastomoses of the marginal artery are least effective (Figure 4B).…”
Section: Discussionmentioning
confidence: 99%